The Effect of Promotion on the Sales Level of PT Pegadaian Syariah CPS Meulaboh - Putra, Yudha Prawira Junistiara; Lestari, Indah (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
The author chose PT Pegadaian Syariah CPS Meulaboh as the location for this research. After identifying the problem, the author determined an initial hypothesis, namely that there was an influence of Promotion on Sales Levels. The population in this study was 17 people and all of them were used as samples to obtain data through distributing questionnaires. Based on the results of Hypothesis Testing using simple linear regression, it is known that the sig value of the variable (X) is 0.001<0.05, so in this case it means that the Promotion variable (X) has a positive and significant influence on the Sales Level variable (Y). Thus it can be concluded that the hypothesis in this research is accepted.